Transformational Energy Futures 2050. Neo-Carbon Energy Societal Scenarios - Sirkka Heinonen; Juho Ruotsalainen; Joni Karjalainen (Finland Futures Research Centre, University of Turku, 2022)
This report presents a set of transformative Neo-Carbon Energy scenarios within a societal context. The scenarios describe how society – social relations, culture, values, economy etc. – may change in a renewable energy system. They depict four different avenues and vistas to the world in 2050 where the energy system is decentralised, based almost 100% on renewable energy and prosumeristic citizens play a central role in a peer-to-peer fashion. The scenarios have been constructed within a Tekes-funded research project Neo-Carbon Energy in co-operation with VTT Technical Research Centre of Finland, Lappeenranta University of Technology (LUT), and Finland Futures Research Centre (FFRC) at University of Turku. The foresight part of the research project explores the futures of an economy based on a new energy system and peer-to-peer society in 2050. The project is one of the strategic research openings of Tekes – the Finnish Funding Agency for Innovation.
The neo-carbon scenarios envision possible futures in which renewable energy is produced in a distributed manner, and in which energy is low-cost, or even no-cost. In each scenario energy is produced mainly by solar and wind and stored in batteries, synthetic methane, and other synthetic hydrocarbons. Renewable energy is used for economic activities, and carbon dioxide from the air is used as a source for plastics, chemicals and medicine. As a whole, this would transform the economy and change its energy system into one that is emissions-free, efficient, low-cost, and sustainable.
The scenarios have been formed using two axes and their extreme end values. The X axis is called “Peer-to-peer” and its end values are Corporate (“centralised”) peer-to-peer and Neo-Communal (distributed) peer-to-peer. The Y axis is called “Ecological awareness” and its end values are Pragmatic ecology and Deep ecology. The resulting four scenarios are called “Radical Startups”, “Value-Driven Techemoths”, “Green DIY Engineers” and “New Consciousness”. The scenarios have been tested through a process of five interactive futures cliniques, international surveys, workshops, focus group discussions, and interviews.
The report also provides a list of 10 key recommendations, as a reflection to the scenarios, for various stakeholders in order to prepare for the emerging renewable energy transformation – to proactively surf on the winning side in this futures turbulence. They can be used to support and test strategies and decision-making for the transition towards renewable energy world, as well as to identify game changers – transformative leadership and pioneering actors for making this transformation happen.
The Neo-Carbon Energy world is a radical transformation towards renewable energy and responsible lifestyles. It is a preferred future, empowered by foresight approach and proactive futures creation, resulting in robust futures resilience.